PENGARUH PEMANFAATAN BEASISWA DENGAN HASIL BELAJAR MAHASISWA JURUSAN TEKNIK SIPIL FT-UNP - 428-434 , Yono Julianto (CIVED, 2014)
ABSTRACT   This study is a descriptive correlational,the aimed to determine the effect of scholarships on learning outcomes of students in the Department of Civil Engineering FT - UNP . The research hypothesis that there is significant utilization of scholarship on studentslearning outcomes. The population in this study all students of Department of Civil Engineering FT - UNP year in 2009 and 2010 who received scholarships in 2012 numbered 27 students . The sampling technique is the total sampling.Based on the results of data analysis performed using the Two Tailed Sampels  Testfrom the analysis of correlation between  X and Y variable obtained rvalue of 0,432. This means that Ho is rejected and Ha accepted . There is effect of scholarships to student learning outcomes . Keywords : gifts, scholarships , study result